Takhrîj al-H?adîth dalam Perspektif Kajian Ontologi dan Aksiologi Ilmu Hadis - Abdul Basid (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2016)
In reading a hadith, it is not enough just to a dictionary and a book of hadith as a reference. This is because the hadith collected in many books of hadith. So as a takhrîj al-h?adîth emerged as a method to track the tradition to the original source. Application of the method takhrîj al-h?adîth has two major variants; conventional (sanad and matn) and modern (computer) . Two variants will certainly have advantages and disadvantages of each.